Going digital: The Spanish experience - León, Bienvenido (Javnost-The Public, 2007)
This article focuses on the political, social and economic trends of the Spanish television system in a moment of transition towards the new digital environment. In 2006, digital television is still in an incipient phase, since less than 25% of the Spanish population have access to digital terrestrial television. In spite of the effort of the government to promote it, there is serious concern about the feasibility of the analogue switch-off scheduled for April 2010. The development of digital TV has shaped an environment in which audience fragmentation and market concentration have increased. But from the point of view of the audience, changes have not been very relevant, as the offer of the new channels is very similar to the already existing and interactive services and contents are very limited.